Geotechnical Properties of Wood Ash-Based Composite Fine-Grained Soil - Bayshakhi Deb Nath; Grytan Sarkar; Sumi Siddiqua; Md. Rokunuzzaman; Md. Rafiqul Islam (Advances in Civil Engineering)
It is observed in Bangladesh that there is an extensive use of wood as a solid biomass for heat and electricity production, which led to increase in the amount of combustion residues known as ash. These ashes are discarded and dumped here and there, resulting in pollution of the environment. It could be managed by using wood ash as a stabilizer of soft clay. It is found that there is an enhancement of the engineering properties of existing soil in stabilized forms particularly unconfined compressive strength (UCS), shear strength parameters, workability, and compaction and compressibility characteristics. Therefore, laboratory tests associated with these properties were performed for some selected percentage of wood ash, for example, 0%, 5%, 7.5%, 10%, and 12.5%. Chemical investigation of wood ash depicts that it contains approximately 30% CaO, which directs it to behave like a pozzolanic material. Besides, the test result signifying that the soil could be made lighter with the increase of moisture content, strength, and reduction of compressibility due to the addition of ash content.